Lead biosorption characterisation of Aspergillus piperis : contextualising the novel fungus within the larger mycoremediation corpus - Brink, Hendrik Gideon (University of Pretoria, 2022)
Dissertation (MEng (Chemical Engineering))--University of Pretoria, 2021.